1991
DOI: 10.1111/j.1744-6570.1991.tb02402.x
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Recruitment in Job Choice: A Different Way of Looking

Abstract: Recent literature reviews have called into question the impact of recruitment activities on applicants’job choices. However, most previous findings have been based on cross‐sectional ratings obtained immediately after initial screening interviews, thus raising questions about the degree to which prior conclusions are bound to that particular methodology. In contrast, the present study used longitudinal structured interviews to let job seekers explain, in their own words, how they made critical job search and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
476
0
15

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 595 publications
(508 citation statements)
references
References 46 publications
17
476
0
15
Order By: Relevance
“…Accordingly, empirical evidence highlights P-O fit perceptions as important predictors of job choice intentions (Cable & Judge, 1994). Rynes, Bretz and Gerhart (1991) found that while job and organizational characteristics are responsible for early perceptions of organization fit, changes in fit assessments are due to more detailed job and/or organizational information. Similar to the arguments supporting realistic job previews (RJP), which are an organization's presentation of both favorable and unfavorable job-related information to job candidates (Rynes, 1991), more specific information may allow applicants to make more informed choices about whether or not to accept offers of employment (Wanous, 1973).…”
Section: Models Of Person-organization (P-o) Fit Have Grown Increasinmentioning
confidence: 99%
“…Accordingly, empirical evidence highlights P-O fit perceptions as important predictors of job choice intentions (Cable & Judge, 1994). Rynes, Bretz and Gerhart (1991) found that while job and organizational characteristics are responsible for early perceptions of organization fit, changes in fit assessments are due to more detailed job and/or organizational information. Similar to the arguments supporting realistic job previews (RJP), which are an organization's presentation of both favorable and unfavorable job-related information to job candidates (Rynes, 1991), more specific information may allow applicants to make more informed choices about whether or not to accept offers of employment (Wanous, 1973).…”
Section: Models Of Person-organization (P-o) Fit Have Grown Increasinmentioning
confidence: 99%
“…The recruitment has majorly focused on source credibility, the role and importance of media credibility has largely been ignored. It is evident from the literature that job incumbents as recruitment sources are perceived to be most credible as they are the ones closely associated with work and have information about job and organizational attributes (Rynes et al 1991). Corporate recruiters are perceived to be less credible as they have an explicit intention of presenting an overly positive image of the organization before the potential applicants.…”
Section: Discussionmentioning
confidence: 98%
“…The realistic information hypothesis proposes that persons recruited via different sources are likely to have more accurate in formation about what the job entails (Rynes et al 1991). Possessing such information enables a candidate to decide whether to proceed with the job and make an informed decision.…”
Section: Realistic Informationmentioning
confidence: 99%
“…I have argued that nepotism is inherently unfair due to the fact that it allows certain individuals a competitive advantage as a function of social connections rather than competence. While it has been shown that applicants who receive special treatment are likely to view the organization more favorably (Rynes et al, 1991), I argued and tested the perceptions of those who did not receive this special treatment. Indeed, applicants who are thinking of applying to a nepotistic organization could ask several important questions.…”
Section: Chapter 4: Discussionmentioning
confidence: 99%